Citogenética de espécies do gênero Scinax (Anura: Hylidae) - Luísa de Paula Reis (2016)
The genus Scinax (Anura, Hylidae) consists of 113 species distributed from eastern to southern Mexico to Argentina and Uruguay; Trinidad and Tobago and St. Lucia. A phylogenetic analysis of the genus led to its into two major clades: S. ruber, composed of the S. rostratus and S. uruguayus groups and species not allocated to any group and the S. catharinae clade, composed of the S. catharinae and S. perpusillus groups. The monophyletism of the S. perpusillus group was nottested. In order to contribute to the recognition of phylogenetic relationships, by providing new characters for analysis, and to the study of chromosome characters evolution, we used the cytogenetic approach. Cytogenetic analyses allow the characterization of chromosome features, have shown great variability in Anura. This work is divided into two chapters. In the first, we describe cytogenetically seven species of S. perpusillus group, including the analysis of the nucleolus organizer regions (NORs) that present inter and intraspecific variation, functioningas a cytotaxonomic marker. In the second chapter, we describe the protocol that we developed for fibroblast culture in anurans, which allows the obtention of better chromosome preparations than direct preparations. We describe the karyotype os Scinax cf. machadoi, obtained from cultured cells